Analisis Kemitraan Terhadap Pendapatan Usaha Petani Jagung Manis - Yudi Gunawan; Yoyo Sunaryo; Siti Wahana (Paradigma Agribisnis, 2024)
Farming activities have a partnership pattern that is considered to be able to help solve farmers' problems with limited capital and access to marketing. Many sweet corn farmers have made partnerships with middlemen. This research was conducted in Gebang Kulon Village with the implementation time from January to June 2023. The research design is descriptive quantitative with research techniques using survey methods. The sampling technique was carried out on a sample size of 114 farmers. Data analysis used descriptive analysis. The results of the analysis show that the condition of sweet corn farming carried out by farmers in one season with a fixed cost of Rp. 3,661,849 and variable costs Rp. 21,951,046 and a total cost of Rp. 25,612,895. The average production of baby corn is 1,470 kg and 13,303 kg of corn on the cob. Judging from the receipt of baby corn Rp. 3,301,620 and corn cobs Rp. 36,995,643. so that the total revenue is about Rp. 40,297,263. The condition means that the farmer's income is Rp. 14,684,368. Analysis of the partnership pattern found that farmers and middlemen partnered based on the principle of mutual trust. Most of the capital provided by middlemen is 50% which is issued to meet the needs of farming costs. The analysis of rights and obligations found that these rights and obligations were carried out in writing, the obligations of the middlemen at the same time were the rights of the partner farmers and the rights of the middlemen at the same time were the obligations of the partner farmers.Keywords: Sweet Corn, Partnership, Farmers, Cirebon